Pseudomagnetic fields for sound at the nanoscale - Brendel, Christian; Peano, Vittorio; Painter, Oskar J.; Marquardt, Florian (Proceedings of the National Academy of Sciences of the United States of America, 2017)
There is a growing effort in creating chiral transport of sound waves. However, most approaches so far have been confined to the macroscopic scale. Here, we propose an approach suitable to the nanoscale that is based on pseudomagnetic fields. These pseudomagnetic fields for sound waves are the analogue of what electrons experience in strained graphene. In our proposal, they are created by simple geometrical modifications of an existing and experimentally proven phononic crystal design, the snowflake crystal. This platform is robust, scalable, and well-suited for a variety of excitation and readout mechanisms, among them optomechanical approaches.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Nanomechanics; Optomechanics; Phononic crystal; Pseudomagnetic field; Topological physics